2014
DOI: 10.14814/phy2.12109
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of angiopoietin-like protein 4 production during and after exercise

Abstract: Angiopoietin‐like protein 4 (ANGPTL4) may regulate lipoprotein lipase‐dependent plasma clearance of triacylglycerol from skeletal muscle during exercise. The aim of this study was to examine the importance of muscle in regulating ANGPTL4 in response to exercise. We sampled muscle biopsies and serum before, immediately after, and 2 h after 45 min of ergometer cycling. Sampling was done before and after a 12‐week training intervention in controls and dysglycemic subjects. Moreover, fat biopsies were taken before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 33 publications
(108 reference statements)
5
49
0
Order By: Relevance
“…However, a chronic exercise intervention combining strength and endurance training for 12 weeks had no effect on basal plasma ANGPTL4 concentrations and skeletal muscle ANGPTL4 mRNA content. 52 In conclusion, ANGPTL4 is highly induced in muscle in response to exercise. However, adipose tissue and the liver may contribute more than muscle to the exerciseinduced increase in circulating ANGPTL4.…”
Section: Skeletal Muscle As the Source Of Myokines And Adipo-myokinesmentioning
confidence: 88%
See 2 more Smart Citations
“…However, a chronic exercise intervention combining strength and endurance training for 12 weeks had no effect on basal plasma ANGPTL4 concentrations and skeletal muscle ANGPTL4 mRNA content. 52 In conclusion, ANGPTL4 is highly induced in muscle in response to exercise. However, adipose tissue and the liver may contribute more than muscle to the exerciseinduced increase in circulating ANGPTL4.…”
Section: Skeletal Muscle As the Source Of Myokines And Adipo-myokinesmentioning
confidence: 88%
“…In a study by Norheim et al, it was reported that 30 min after an acute bout of endurance exercise, ANGPTL4 mRNA expression was significantly higher in overweight dysglycemic subjects compared to lean controls at the beginning of the intervention study. 52 Interestingly, they found that ANGPTL4 mRNA expression was much higher in adipose tissue than muscle. Following 12 weeks of combined endurance and resistance training, adipose tissue mRNA expression of ANGPTL4 as well as basal plasma levels was unchanged in both groups.…”
Section: Exercise and The Production Of Adipokines By Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…RNA integrity was determined using Agilent RNA 6000 Nano Chips and a Bioanalyzer 2100. Deep sequencing was performed with the Illumina HiSeq 2000 system with multiplexed design [22]. The cDNA was fragmented, and cDNA fragments with 51 bp nucleotides were selected and amplified.…”
Section: Methodsmentioning
confidence: 99%
“…The expression level of ANGPTL‐4 depends on nutritional status and human plasma ANGPTL‐4 increases after long‐term fasting, chronic caloric restriction, and following physical activity . These three situations have as a common feature of elevated plasma FFA levels.…”
Section: Introductionmentioning
confidence: 99%